Use of Polyelectrolytes for the Fabrication of Porous NiO Films by Electrophoretic Deposition for Supercapacitor Electrodes. (1st September 2016) - Gonzalez, Z.; Ferrari, B.; Sanchez-Herencia, A.J.; Caballero, A.; Morales, J.
Abstract: Different polyelectrolyte multilayers of Polyethilenimine (PEI) and Polyacrylic Acid (PAA) have been assembled onto β-Ni(OH)2 nanoplatelets using a simple one-pot route by means of consecutive adsorption (Layer by layer method, LbL). The increase of the number of the layers, from 1 to 5, has been varied to tune the microstructure of supercapacitor electrodes and try to improve their physical properties (specific surface, porosity, etc.) which would increase the specific capacitance in the final device. For this, three stabilized suspensions, prepared with modified nanoplatelets with 1, 3 and 5 layers, were shaped by Electrophoretic Deposition (EPD) onto Ni foils and Ni foam. The effect of the LbL on the final microstructure of the ceramic semiconductor material was evaluated in terms of pseudocapacitance.